(3TQM QSGdI GdJhMjO ddHQchjs - (3GdHQcGJj, ehSi Hf CMeO GdHQcGJj, cGf MjG (B1151 (3g`s ((3YKeGf Hf eMeOs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj dG Edg ShGg hHYO ajbhd GdabjQ ehSi Hf CMeO GdHQcGJj GdfcjOj deG cGf fLGI Gdcd aj Gdcd HGYJbGO cdeI GdJhMjO GdeSeGI HcdeI GdENdGU hcGf eQhjI aj HjGf eYfGgG Yf GdHQchj GdeMJGLI Edi GdTQM aTQYJ dgs
(3BNQgG (B:s
(3Ef gPG Gdeaghe ehLhO aj Gddg JYGdi ceG aUdfGg aj GdebOeI abO bGdgG hgh eDef Cj agh eDef MbG hMce eWGHb ddhGbY hdG jdRegG dJfGbVs
(3fSNI efbhdI Yf fSNI GdeDda eDQNI H SfI (B1151 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 8 929s
(3gOjI GdYGQajf (B2 / 482s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds